Shifting Stacks A Look at the Future of Theological Libraries in Celebration of Atla's 75th Anniversary - Collins, Matthew; Estes, James; Stephens, Myka Kennedy (Atla Open Press, 2020)
Shifting Stacks examines emergent issues at the nexus of academic librarianship and theological education. It seeks to facilitate and inspire forward-thinking conversation that may guide a reorientation of theological and religious studies librarianship that is adaptive and responsive to change and emerging needs in librarianship, theological education, and the broader global community. The need for substantive conversation on these topics has grown more important and critical as the effects of the current global pandemic ripple through our institutions. Shifting Stacks includes an introduction by James Estes and Myka Kennedy Stephens, and contributions from Christopher A. Rogers (transformational theological literacy), Andrew Keck (open access publishing), Paul A. Tippey (digital libraries), Shawn Goodwin and Evan Kuehn (topic modeling), Megan Welsh and Alexander Luis Odicino (collection development), Stephen D. Crocco (transitioning libraries), Kerrie Stevens and Siong Ng (ANZTLA-Atla relationship), and Carisse Mickey Berryhill (forward-looking reflection).